Physico - Chemical Analysis of Macro & Micro Elements of Soils of Various Sites around Cement Industry in Rae Bareli District, UP, India (International Journal of Innovative Research in Engineering & Management, 2023)
The study undertaken during the year 2021 –2022 (July to April), deals with thorough chemical  investigation of soil samples collected from different study  sites around cement industry in varying seasons, located in  Raebareli District. Samples estimated in a regular interval of  3 months (July, Oct, Jan & April) for seasonal variations.  The dust emitted from the Cement Company, located in  Raebareli, gets deposited in course of time over the soil,  leaves and forms a grey cover on the surrounding soils. The  concentration of micro nutrient Fe, Cr, Zn, Cu is very high  in most of the sampling sites. Extremely high concentration  of Fe (60 to 200 ppm) and Cr (72 to 99 ppm) reported almost  in all seasons. pH showed highly alkaline (8.2 to 11.3) nature  of soil.
Keywords: Soils; Cement; Dust; AAS (Atomic Absorption Spectrophotometer); pH; Heavy metals